2018
DOI: 10.28982/josam.393143
|View full text |Cite
|
Sign up to set email alerts
|

The influence of anemia on maternal and neonatal outcomes in adolescent pregnant

Abstract: The aim of this study was to investigate the influence of anemia on maternal and neonatal outcomes in adolescent pregnant. Methods: The files of 1407 adolescent women who gave birth in our hospital, from January 2010 to June 2015 were retrospectively investigated. Demographic characteristics, hemoglobin concentrations before birth, obstetric and neonatal outcomes were evaluated. Results: The mean age of the study group was 17.95±1.09 years. Anemia frequency was found as 36%. Anemia was significantly higher wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 20 publications
(37 reference statements)
0
4
0
Order By: Relevance
“…Frass in her study reported that postpartum hemorrhage was related to Hb levels at labor and the severity of anaemia was an important factor that causes greater blood loss and adverse maternal outcomes. (44) Similarly, studies done by Kavle et al, (45) and Yılmaz et al, (46) found that anaemia increased the incidence of hemorrhage during pregnancy. A possible explanation for this finding is that women with anaemia are more likely to have uterine atony due to impaired transport of oxygen and Hb to the uterus.…”
Section: Discussionmentioning
confidence: 78%
“…Frass in her study reported that postpartum hemorrhage was related to Hb levels at labor and the severity of anaemia was an important factor that causes greater blood loss and adverse maternal outcomes. (44) Similarly, studies done by Kavle et al, (45) and Yılmaz et al, (46) found that anaemia increased the incidence of hemorrhage during pregnancy. A possible explanation for this finding is that women with anaemia are more likely to have uterine atony due to impaired transport of oxygen and Hb to the uterus.…”
Section: Discussionmentioning
confidence: 78%
“…Likewise, the risk of poor neonatal outcomes such as low birth weight [ 3 , 4 , 13 , 16 ], small-for-gestational-age [ 3 , 5 , 13 ], preterm birth [ 3 , 4 , 6 , 12 , 13 ], low Apgar score [ 3 , 5 , 6 ], stillbirth [ 12 , 13 ], and neonatal and perinatal mortality [ 5 , 13 , 16 ] is higher among neonates and children born to anemic mothers. In addition, low maternal hemoglobin level during pregnancy was also found to increase the risk of placenta previa [ 5 ] and abruption, fetal malformation, growth restriction [ 12 ], and neonatal admission [ 6 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Además, se asoció a la hemorragia postparto, parto por cesárea, oligohidramnios y trastorno hipertensivo del embarazo, resultado, en la mayoría de casos, de la relajación de la fibra muscular del útero por hipoxia secundaria a los niveles bajos de hemoglobina. La evidencia disponible coincide con dichos resultados, al respecto Uzunov et al 18 identificaron asociación entre anemia y el parto por cesárea (p= 0.001), así también Basbug y Sonmez 20 refirieron asociación con trastornos hipertensivos (p = 0.01) mientras Yilmaz et al 21 evidenciaron asociación significativa entre anemia y hemorragia postparto (p= 0.003). Ver en tabla 8.…”
Section: Discussionunclassified
“…Entre las pacientes anémicas se observó preeclampsia mientras que el grupo no anémico se presentó en menor frecuencia; la diferencia fue estadísticamente significativa. Yilmaz et al 21 , 2018, realizaron un estudio "The influence of anemia on maternal and neonatal outcomes in adolescent pregnant", cuyo objetivo fue evaluar la influencia de la anemia en los resultados maternos y neonatales en adolescentes embarazadas. En materiales y métodos, la metodología de estudio fue analítico, retrospectivo, la población estuvo conformada por 1407 adolescentes embarazadas.…”
Section: Internacionalesunclassified
See 1 more Smart Citation